Development and validation of taxonomy of affective events at work - Junça Silva, A.; Caetano, António; Lopes, M. (IX ISQOLS Conference: Discovering new frontiers in Quality-of-life Research, 2012)
Affective events theory (Weiss, & Cropanzano, 1996) highlights the importance of affective events at work as antecedents of several emotional experiences, employees´ work related behaviours and attitudes. However, a comprehensive picture on the kind of events that occur frequently in the workplace and a universally valid approach regarding the assessment of work events is lacking. The aim of this study was to develop a comprehensive taxonomy of affective events. As such, we conducted semi-structured interviews with design and format based on previous research (Basch, & Fisher, 1998; Fitness, 2000). Participants described events at work that had caused them to experience specific emotions. All responses were transcribed, analyzed and then sorted into general categories according to their thematic similarity. We identified 7 categories of negative job-related events and 6 categories of positive job-related events. Overall, were reported 229 daily events, (133 positive and 96 negative events). The largest overall positive event category was “interpersonal interaction”. Within this category, the most frequent event was “having a good time and laughing”. The most frequent overall negative category was “operational hassles”. The most frequent event was “having a poor performance on a task”. This study adds to previous research by providing a comprehensive yet parsimonious classification of both positive and negative affective events.